Development and analysis of a SmPC-based machine-readable dataset of contraindications for clinical decision support and real-world data analysis - Miriam Schechner; Wahram Andrikyan; Thomas Bauerdick; Theresa Terstegen; Louisa Redeker; Martin Federbusch; Katrin Farker; Alexander Strübing; Florian Schmidt; Petra Thürmann; Sven Schmiedl; Hanna M. Seidling; et al. (European Journal of Clinical Pharmacology, 2026)
Purpose Unrecognized contraindications pose risks for adverse drug reactions, hospitalizations or death. Clinical decision support systems (CDSS) aim to mitigate medication-related harm, particularly originating from contraindications. However, many CDSS provide limited benefit, as they focus largely on singular risk situations such as drug-drug interactions and often generate alerts of limited clinical relevance. Comprehensive integration of contraindications into CDSS may support more clinically meaningful alerts. The aim of this work was the development and analysis of machine-readable contraindication lists, including drug-clinical condition, drug-kidney function and drug-drug (group) contraindications, for integration into CDSS and real-world data analysis. Methods We extracted and operationalized contraindications, based on Summaries of Product Characteristics (SmPCs), of the 688 most prescribed drugs in Germany, leveraging common medical coding systems. Moreover, we analyzed extracted contraindications based on operationalizability, overall frequency and frequencies within different contraindication categories. Results In total, we extracted 4676 contraindications, of which 2129 (45.5%) were deemed operationalizable. Of these 2129 contraindications, 1652 (77.6%) were attributed to drug-clinical condition, 83 (3.9%) to drug-kidney, 140 (6.6%) to drug-drug group and 254 (11.9%) to drug-drug. The most frequently mentioned contraindicated risk situations were ‘severe liver insufficiency’ ( n = 74, 3.5%), ‘pregnancy’ ( n = 66, 3.1%), ‘MAO-inhibitors’ ( n = 44, 2.1%), and ‘shock’ ( n = 44, 2.1%). Conclusion Our results show, that drug-clinical condition contraindications are listed far more frequently in SmPCs than other contraindication categories. Focusing on clinical condition-related contraindications within CDSS could improve the detection of clinically relevant contraindications in routine data and enhance medication safety. The clinical applicability is currently being evaluated in the INTERPOLAR study.

Protein phosphatase 2A impairs cardiac uptake of glucose in the mammalian heart - Katarina Hadova; Daniel Gündel; Torsten Knieß; Peter Brust; Jan Klimas; Joachim Neumann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Protein phosphatase 2A (PP2A) accounts for approximately half of all serine/threonine phosphatase activity in the mammalian heart. We hypothesised that PP2A, through dephosphorylation of key regulatory enzymes, modulates cardiac glucose uptake and metabolism in vivo. Using positron emission tomography (PET), we studied the uptake of 2-[ 18 F]fluoro-2-deoxy-D-glucose ([ 18 F]FDG) in living mice with cardiac-specific overexpression of the catalytic subunit of PP2A (PP2A-TG) as well as in littermate controls (wild-type, WT). Additionally, we analysed the expression of enzymes and transcription factors involved in cardiac glucose metabolism. Cardiac glucose consumption was reduced by 41% ( P < 0.05) in PP2A-TG mice relative to WT. Real-time quantitative polymerase chain reaction analysis revealed decreased gene expression of glycogen synthase 1 (− 26%, P < 0.05), glycogen phosphorylase (− 17%, P < 0.05), Mtor (-22%, P < 0.05), peroxisome proliferator-activated receptor gamma (Pparg), and its coactivator PGC-1α (-41% and − 28% respectively; both P < 0.05) in PP2A-TG hearts. Western blotting demonstrated increased protein expression of phosphoinositide 3-kinase (PI3K, 26%, P < 0.05), reduced expression of glycogen synthase (-34%, P < 0.05) and glycogen phosphorylase (-18%, P < 0.05), and enhanced phosphorylation of AKT (95%, P < 0.05) and glycogen synthase kinase-3β (GSK3β, 22%, P < 0.05) in PP2A-TG hearts. These findings indicate that PP2A impairs cardiac glucose metabolism in vivo through modulation of multiple components of glucose handling, including the PI3K/AKT signalling axis, glycogen metabolism, and PPARγ-dependent transcriptional regulation. The effects of PP2A appear to be predominantly indirect. Elevated PP2A expression may therefore be detrimental in heart failure by compromising myocardial energy production.

Elevated alpha-1 antitrypsin and C-reactive protein: association on all-cause and cause-specific mortality in older adults - Cammie Tran; Hans G. Schneider; Que T. Lam; Johannes T. Neumann; Flavia Cicuttini; Chenglong Yu; Zhen Zhou; Mark R. Nelson; Andrew M. Tonkin; Daniel Clayton-Chubb; Sultana Monira Hussain; Peter D. Fransquet; et al. (GeroScience, 2025)

Unravelling sources of fecal pollution in oligotrophic mountain waters: Integrating Escherichia coli enumeration, microbial source tracking, and eDNA analysis - Sharon Maes; Martin Andersson-Li; Jessica Sjöstedt; Jon Hildahl; Daniel Yu; Norman Neumann; Monica Odlare; Anders Jonsson (Environmental Monitoring and Assessment, 2025)
Aquatic ecosystems in mountainous regions are crucial for fulfilling natural and anthropogenic water demands around the world. This study integrates Escherichia coli ( E. coli ) enumeration, microbial source tracking (MST), and environmental DNA (eDNA) analysis to identify sources of fecal contamination in oligotrophic mountain waters. Conducted in an area with intense tourism and traditional reindeer herding, this research addresses the urgent need to identify fecal pollution sources to safeguard the water quality of these vital ecosystems. Our study reveals that E. coli levels vary significantly across different locations and times, suggesting varied sources of contamination from humans, wildlife, and livestock animals. MST techniques, alongside eDNA analysis, provided insights into the complex patterns of fecal pollution, allowing for the distinction between human and animal contributions to water contamination. Our findings highlight the importance of combining various analytical methods to track fecal pollution sources effectively, and to develop targeted strategies for water quality management.

Geochemical analysis of lateritic duricrust formation in the Cuesta and Paulista Peripheral Depression sectors of São Paulo State, southeastern Brazil - Everton Tiago Sulato; Karen Luko-Sulato; Daniel Godoy; Reiner Neumann; Vania Rosolen (Journal of South American Earth Sciences, 2025)

Mobility of Sediment and Phosphorus in a Small Stream During Artificial Flood Wave - Martin Neumann; Barbora Jáchymová; Petr Koudelka; Tomáš Dostál; Miroslav Bauer; Josef Krása; Tomáš Laburda; Pavel Rosendorf; Daniel Fiala; Karina Bynum; John S. Schwartz; David Zumr (Environmental Processes, 2025)
This study investigates the dynamics of sediment and phosphorus transport in small streams affected by recurrent flood waves. The experiments were carried out in two streams with contrasting conditions: one in an agricultural headwater section, which serves as a sediment source, and the other in a mid-water section influenced by fish ponds. High-frequency data on suspended sediment and phosphorus concentrations were collected during several flood waves to assess how floods affect the transport regime, including the role of small reservoirs. The results showed that even initially clear water can mobilize significant amounts of sediment from the riverbed when discharge increases. Sediment mobilization was strongest at the beginning of the flood wave, with concentrations peaking early and then decreasing. Successive floods without additional sediment input led to a decrease in sediment concentrations, as the stream had already flushed out the available sediments. Hysteresis loops showed that most of the sediment transport occurred during the rising part of the flood wave, indicating that the sediment originated from the nearby streambed areas. Phosphorus was mobilized simultaneously with the sediment, and an almost linear relationship was observed between sediment concentration and total phosphorus ( r = 0.979, p < 0.0001). However, only a fraction of the phosphorus was dissolved, so most of the phosphorus was bound to the sediment particles. Soluble reactive phosphorus showed a weaker correlation with sediment concentration ( r = 0.272, p = 0.047). This shows how important it is to consider both sediment dynamics and phosphorus mobilization in event-based flood models.

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Landscape structure affects temporal dynamics in the bumble bee virome: Landscape heterogeneity supports colony resilience - Laura Bosco; Orlando Yañez; Alexandria Schauer; Corina Maurer; Samuel A. Cushman; Raphaël Arlettaz; Alain Jacot; Torsten Seuberlich; Peter Neumann; Daniel Schläppi (Science of The Total Environment, 2024)

Irrigation and oil palm empty fruit bunch mulch enhance eggplant growth, radiation interception and dry matter yield - John Bright Amoah Nyasapoh; Eric Oppong Danso; Daniel Selorm Kpodo; William Amponsah; Emmanuel Arthur; Edward Benjamin Sabi; Peter Bilson Obour; William Akortey; Bernard Kwabena Boadi Mensah; Grace Elorm Ayayi; Mathias Neumann Andersen (European Journal of Agronomy, 2024)

Nitrogen isotope homogenization of dissolved ammonium with depth and 15N enrichment of ammonium during incorporation into expandable layer silicates in organic-rich marine sediment from Guaymas Basin, Gulf of California - Toshiro Yamanaka; Arisa Sakamoto; Kanon Kiyokawa; Jaeguk Jo; Yuji Onishi; Yoshihiro Kuwahara; Ji-Hoon Kim; Lucie C. Pastor; Andreas Teske; Daniel Lizarralde; Tobias W. Höfig; Ivano W. Aiello; et al. (Chemical Geology, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Mineralization kinetics of biosiliceous sediments in hot subseafloors - Ivano W. Aiello; Tobias W. Höfig; Armelle Riboulleau; Andreas P. Teske; Daniel Lizarralde; Jeanine L. Ash; Diana P. Bojanova; Martine D. Buatier; Virginia P. Edgcomb; Christophe Y. Galerne; Swanne Gontharet; Verena B. Heuer; et al. (Geochimica et Cosmochimica Acta, 2024)

Effect of pH and current density on the physical properties of cobalt obtained by electrowinning from sulfate solutions - Fabiano Augusto Costa Mafra Passos; Jonas da Cruz Trajano de Souza; Iranildes Daniel dos Santos; Reiner Neumann; Pedro Paulo Medeiros Ribeiro; Achilles Junqueira Bourdot Dutra (Minerals Engineering, 2024)

Letter to the editor regarding Collard et al. (2023): “Persistence and mobility (defined as organic-carbon partitioning) do not correlate to the detection of substances found in surface and groundwater: Criticism of the regulatory concept of persistent and mobile substances” - Hans Peter H. Arp; Raoul Wolf; Sarah E. Hale; Sivani Baskaran; Juliane Glüge; Martin Scheringer; Xenia Trier; Ian T. Cousins; Harrie Timmer; Roberta Hofman-Caris; Anna Lennquist; André D. Bannink; et al. (Science of The Total Environment, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Canonical circuit computations for computer vision - Daniel Schmid; Christian Jarvers; Heiko Neumann (Biological Cybernetics, 2023)
Advanced computer vision mechanisms have been inspired by neuroscientific findings. However, with the focus on improving benchmark achievements, technical solutions have been shaped by application and engineering constraints. This includes the training of neural networks which led to the development of feature detectors optimally suited to the application domain. However, the limitations of such approaches motivate the need to identify computational principles, or motifs, in biological vision that can enable further foundational advances in machine vision. We propose to utilize structural and functional principles of neural systems that have been largely overlooked. They potentially provide new inspirations for computer vision mechanisms and models. Recurrent feedforward, lateral, and feedback interactions characterize general principles underlying processing in mammals. We derive a formal specification of core computational motifs that utilize these principles. These are combined to define model mechanisms for visual shape and motion processing. We demonstrate how such a framework can be adopted to run on neuromorphic brain-inspired hardware platforms and can be extended to automatically adapt to environment statistics. We argue that the identified principles and their formalization inspires sophisticated computational mechanisms with improved explanatory scope. These and other elaborated, biologically inspired models can be employed to design computer vision solutions for different tasks and they can be used to advance neural network architectures of learning.

Urinary concentrations of metals before and after volcanic eruption: a natural experiment surrounding the eruption of Volcán de Fuego, 2018 - Natalie R. Neumann; Jaime Butler-Dawson; Lyndsay Krisher; Diana Jaramillo; Daniel Pilloni; Greg Waite; Yaqiang Li; Stephen B. Wittels; Kathrin Schilling; Lee S. Newman; Katherine A. James (Environmental Geochemistry and Health, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Complex and flexible catabolism in Aromatoleum aromaticum pCyN1 - Patrick Becker; Annemieke Döhmann; Lars Wöhlbrand; Daniela Thies; Christina Hinrichs; Ramona Buschen; Daniel Wünsch; Meina Neumann‐Schaal; Dietmar Schomburg; Michael Winklhofer; Richard Reinhardt; Ralf Rabus (Environmental Microbiology, 2022)
Summary Large quantities of organic matter are continuously deposited, and (a)biotic gradients intersect in the soil–rhizosphere, where biodegradation contributes to the global cycles of elements. The betaproteobacterial genus Aromatoleum comprises cosmopolitan, facultative denitrifying degradation specialists. Aromatoleum aromaticum . pCyN1 stands out for anaerobically decomposing plant‐derived monoterpenes in addition to monoaromatic hydrocarbons, polar aromatics and aliphatics. The catabolic network's structure and flexibility in A . aromaticum pCyN1 were studied across 34 growth conditions by superimposing proteome profiles onto the manually annotated 4.37 Mbp genome. Strain pCyN1 employs three fundamentally different enzymes for C–H‐bond cleavage at the methyl groups of p ‐cymene/4‐ethyltoluene, toluene and p ‐cresol respectively. Regulation of degradation modules displayed substrate specificities ranging from narrow (toluene and cyclohexane carboxylate) via medium‐wide (one module shared by p ‐cymene, 4‐ethyltoluene, α‐phellandrene, α‐terpinene, γ‐terpinene and limonene) to broad (central benzoyl‐CoA pathway serving 16 aromatic substrates). Remarkably, three variants of ATP‐dependent (class I) benzoyl‐CoA reductase and four different β‐oxidation routes establish a degradation hub that accommodates the substrate diversity. The respiratory system displayed several conspicuous profiles, e.g. the presence of nitrous oxide reductase under oxic and of low‐affinity oxidase under anoxic conditions. Overall, nutritional versatility in conjunction with network regulation endow A . aromaticum pCyN1 with broad adaptability.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Genome sequencing in families with congenital limb malformations - Jonas Elsner; Martin A. Mensah; Manuel Holtgrewe; Jakob Hertzberg; Stefania Bigoni; Andreas Busche; Marie Coutelier; Deepthi C. de Silva; Nursel Elçioglu; Isabel Filges; Erica Gerkes; Katta M. Girisha; et al. (Human Genetics, 2021)
The extensive clinical and genetic heterogeneity of congenital limb malformation calls for comprehensive genome-wide analysis of genetic variation. Genome sequencing (GS) has the potential to identify all genetic variants. Here we aim to determine the diagnostic potential of GS as a comprehensive one-test-for-all strategy in a cohort of undiagnosed patients with congenital limb malformations. We collected 69 cases (64 trios, 1 duo, 5 singletons) with congenital limb malformations with no molecular diagnosis after standard clinical genetic testing and performed genome sequencing. We also developed a framework to identify potential noncoding pathogenic variants. We identified likely pathogenic/disease-associated variants in 12 cases (17.4%) including four in known disease genes, and one repeat expansion in HOXD13 . In three unrelated cases with ectrodactyly, we identified likely pathogenic variants in UBA2 , establishing it as a novel disease gene. In addition, we found two complex structural variants (3%). We also identified likely causative variants in three novel high confidence candidate genes. We were not able to identify any noncoding variants. GS is a powerful strategy to identify all types of genomic variants associated with congenital limb malformation, including repeat expansions and complex structural variants missed by standard diagnostic approaches. In this cohort, no causative noncoding SNVs could be identified.

Cost‐effectiveness of longitudinal surveillance for Piscirickettsia salmonis using qPCR in Atlantic salmon farms ( Salmo salar ) in Chile - Marina K. V. C. Delphino; Fernando O. Mardones; Joaquin Neumann Heise; Alicia Gallardo; Daniel Jimenez; Andrea Peña; Marco Rozas‐Serri; Ian A. Gardner (Journal of Fish Diseases, 2021)
Costs of diagnostic testing including sample collection, sampling frequency and sample size are an important consideration in the evaluation of the economic feasibility of alternative surveillance strategies for detection of infectious diseases in aquatic animals. In Chile, Piscirickettsia salmonis is the primary reason for antibiotic treatments in farmed Atlantic salmon. In 2012, a surveillance and control programme for piscirickettsiosis was established with an overall goal of reducing antibiotic use. The present study estimated the cost‐effectiveness of different sampling frequencies and sample sizes to achieve at least 95% confidence of early detection of P. salmonis at the netpen and farm levels using a validated qPCR test. We developed a stochastic model that incorporated variability in test accuracy, within‐pen prevalence and sampling costs. Our findings indicated that the current piscirickettsiosis surveillance programme based on risk‐based sampling of five moribund or dead fish from 2 to 3 netpens is cost‐effective and gives a high probability of detection of P. salmonis in Atlantic salmon farms in Chile at both the netpen and farm levels. Results from this study should incentivize salmon farmers to establish cost‐effective strategies for early detection of P. salmonis infection and the application of this approach to other highly infectious diseases.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Ventilation of the northern Baltic Sea - Thomas Neumann; Herbert Siegel; Matthias Moros; Monika Gerth; Madline Kniebusch; Daniel Heydebreck (Ocean Science, 2020)
The Baltic Sea is a semi-enclosed, brackish water sea in northern Europe. The deep basins of the central Baltic Sea regularly show hypoxic conditions. In contrast, the northern parts of the Baltic Sea, the Bothnian Sea and Bothnian Bay, are well oxygenated. Lateral inflows or a ventilation due to convection are possible mechanisms for high oxygen concentrations in the deep water of the northern Baltic Sea. In March 2017, conductivity–temperature–depth (CTD) profiles and bottle samples, ice core samples, and brine were collected in the Bothnian Bay. In addition to hydrographic standard parameters, light absorption has been measured in all samples. A complementary numerical model simulation provides quantitative estimates of the spread of newly formed bottom water. The model uses passive and age tracers to identify and trace different water masses. Observations indicate a recent ventilation of the deep bottom water at one of the observed stations. The analysis of observations and model simulations shows that the Bothnian Bay is ventilated by dense water formed due to mixing of Bothnian Sea and Bothnian Bay surface water initializing lateral inflows. The observations show the beginning of the inflow and the model simulation demonstrates the further northward spreading of bottom water. These events occur during wintertime when the water temperature is low. Brine rejected during ice formation barely contributes to dense bottom water.

Quantifying the contribution of shipping NO x emissions to the marine nitrogen inventory – a case study for the western Baltic Sea - Daniel Neumann; Matthias Karl; Hagen Radtke; Volker Matthias; René Friedland; Thomas Neumann (Ocean Science, 2020)
The western Baltic Sea is impacted by various anthropogenic activities and stressed by high riverine and atmospheric nutrient loads. Atmospheric deposition accounts for up to a third of the nitrogen input into the Baltic Sea and contributes to eutrophication. Amongst other emission sources, the shipping sector is a relevant contributor to the atmospheric concentrations of nitrogen oxides (NOX) in marine regions. Thus, it also contributes to atmospheric deposition of bioavailable oxidized nitrogen into the Baltic Sea. In this study, the contribution of shipping emissions to the nitrogen budget in the western Baltic Sea is evaluated with the coupled three-dimensional physical biogeochemical model MOM–ERGOM (Modular Ocean Model–Ecological ReGional Ocean Model) in order to assess the relevance of shipping emissions for eutrophication. The atmospheric input of bioavailable nitrogen impacts eutrophication differently depending on the time and place of input. The shipping sector contributes up to 5 % to the total nitrogen concentrations in the water. The impact of shipping-related nitrogen is highest in the offshore regions distant from the coast in early summer, but its contribution is considerably reduced during blooms of cyanobacteria in late summer because the cyanobacteria fix molecular nitrogen. Although absolute shipping-related total nitrogen concentrations are high in some coastal regions, the relative contribution of the shipping sector is low in the vicinity of the coast because of high riverine nutrient loads.

Indicator-Based Soil Moisture Monitoring of Wetlands by Utilizing Sentinel and Landsat Remote Sensing Data - Randolf Klinke; Helga Kuechly; Annett Frick; Michael Förster; Tobias Schmidt; Ann-Kathrin Holtgrave; Birgit Kleinschmit; Daniel Spengler; Carsten Neumann (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2018)

Native plasmids restrict growth of Phaeobacter inhibens DSM 17395: Energetic costs of plasmids assessed by quantitative physiological analyses - Kathleen Trautwein; Sabine Eva Will; Reiner Hulsch; Uwe Maschmann; Katharina Wiegmann; Michael Hensler; Victoria Michael; Hanna Ruppersberg; Daniel Wünsch; Christoph Feenders; Meina Neumann‐Schaal; Sabine Kaltenhäuser; et al. (Environmental Microbiology, 2016)
Summary Plasmid carriage is associated with energetic costs, and thus only those plasmids providing fitness benefits are stably maintained in the host lineage. Marine bacteria of the Roseobacter clade harbor up to 11 extrachromosomal replicons, adding lifestyle‐relevant and possibly habitat success‐promoting functions to their genomic repertoire. Phaeobacter inhibens DSM 17395 is a nutritionally versatile representative, carrying three stable and functionally distinct plasmids (65, 78, and 262 kb). The present study investigates the physiological and energetic consequences of plasmid carriage in P. inhibens DSM 17395, employing mutants cured from all native plasmids in every possible combination (seven different). Cultivation in process‐controlled bioreactors with casamino acids as organic substrate revealed a complex physiological response, suggesting existence of functional interconnections between the replicons. Deletion of the 262 kb plasmid boosted growth rate (>3‐fold) and growth efficiency (yields for carbon, O 2 and CO 2 ), which was not observed for the 65 or 78 kb plasmid. Carriage of the 262 kb plasmid was most costly for the wild type, i.e. contributing ∼50% to its energetic (dissimilatory) expenditures. Cost–benefit analysis of plasmid carriage reflects the high value of plasmids for niche specialization of P. inhibens DSM 17395 and most likely also for related Phaeobacter species.

Use of high-throughput RT-qPCR to assess modulations of gene expression profiles related to genomic stability and interactions by cadmium - Bettina Maria Fischer; Daniel Neumann; Ann Liza Piberger; Sarah Fremgaard Risnes; Beate Köberle; Andrea Hartwig (Archives of Toxicology, 2016)

The non-indigenous medusa Blackfordia virginica (Hydrozoa, Leptothecata) in tropical Brazil: 50 years of unnoticed presence - Milena Freire; Gabriel Nestor Genzano; Sigrid Neumann-Leitão; Carlos Daniel Pérez (Biological Invasions, 2014)

Effect of light wavelength on motility and magnetic sensibility of the magnetotactic multicellular prokaryote ‘Candidatus Magnetoglobus multicellularis’ - Lyvia Vidinho de Azevedo; Henrique Lins de Barros; Carolina Neumann Keim; Daniel Acosta-Avalos (Antonie van Leeuwenhoek, 2013)

Assessing Sea-Level Rise Impacts: A GIS-Based Framework and Application to Coastal New Jersey - James E. Neumann; Daniel E. Hudgens; John Herter; Jeremy Martinich (Coastal Management, 2010)